Crisis and constitutional politics in Central Europe - Peter Smuk (Frontiers in Political Science)
This paper aims to examine the impact of significant crisis situations on the constitutional framework over the past decade, including financial crisis, migration, pandemics and war. The paper focuses on the Visegrad countries, especially Hungary, and analyses the constitutional amendments adopted and the relevant constitutional court decisions. By examining the justifications for the amendments and decisions, it is possible to observe the efforts of legislators and governing parties to overcome difficult governance situations in crisis management. The study aims to interpret the relationship between constitutional responses to social crises and crises of democratic political systems, and argues that the inherent feature of constitutional changes triggered by crises is that they remain part of the political system in the longer term. In turn, their impact determines not only the resilience of states and societies, but also the direction in which democratic systems evolve.